A Mid-Miocene erosional unconformity from the Durban Basin, SE African margin: A combination of global eustatic sea level change, epeirogenic uplift, and ocean current initiation. (September 2017) - Hicks, Nigel; Green, Andrew
Abstract: Erosional unconformity surfaces are key indicators for the variations in eustatic sea level, ocean dynamics and climatic conditions which significantly affect depositional environments of sedimentary successions. Using a dense grid of 2D seismic data, we present new evidence from a frontier basin, the offshore Durban Basin, of a mid-Miocene age erosional unconformity that can be correlated with analogous horizons around the entire southern African continental margin. In the Durban Basin, this unconformity is typified by the incision of a mixed carbonate-siliciclastic wedge and ramp margin by a series of submarine canyons. Epeirogenic uplift of southern Africa characterised this period, with erosion and sediment bypass offshore concomitant with increases in offshore sedimentation rates. Although epeirogenic uplift appears to be the dominant mechanism affecting formation of the identified sequence boundary, it is postulated that an interplay between global eustatic sea-level fall, expansion of the east Antarctic ice sheets, and changes in deep oceanic current circulation patterns may have substantially contributed to erosion during this period. Highlights: Reveal an undocumented Mid-Miocene unconformity within the Mesozoic Durban Basin, eastern margin of southern Africa. Takes the form of a series of buried submarine canyons. Canyon morphology is discussed in light of sediment influx and incipient slope architecture. Correlated with a phase of hinterland uplift, global eustatic sea level fall and changes in global oceanographic conditions.